The 'Incense Road' from Petra to Gaza: an analysis using GIS and Cost functions. Issue 2 (1st February 2020) - Zohar, Motti; Erickson-Gini, Tali
ABSTRACT: As early as the fourth century BCE, the Nabateans established the Incense Road to facilitate the transport of aromatic substances (frankincense and myrrh) from the Arabian Peninsula to the Mediterranean basin. An important part of this road was the segment between Petra and Gaza. Although studied before, the accurate route of parts of this segment is still vague since evidence of Roman milestones are scarce and significant portions of the landscape have changed dramatically in modern times, essentially wiping out the tracks of ancient roads. In this study, we use Geographic Information Systems (GIS) and Least Cost Path (LCP) analyses for reconstructing the original path of the Incense Road as well as verifying the factors influencing its establishment. The implemented analyses support the archeological evidence of two travel phases between Petra and Oboda (Avdat): During the first phase the Nabateans used the Darb es-Sultan route; during the second phase, from the first century BCE onwards, they passed through the Ramon Crater. This is the first time such reconstruction is made in the southern Levant. It was found that slope degree and the distance to water resources are dominant factors in reconstructing the accurate path of the Incense Road.